Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Pegawai Yang Dimediasi Oleh Kepuasan Kerja Pada Bagian Kesejahteraan Rakyat Sekretariat Daerah Kabupaten Malang - Nirza, Achmad Hudzaifah Abiyyu; Khalikussabir, Khalikussabir; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the effect of training and motivation on employee performance with job satisfaction as a mediating variable in the People's Welfare Section of the Regional Secretariat of Malang Regency. This research uses a quantitative approach with a survey method through distributing questionnaires to 31 respondents who are employees in the section. The results showed that training and motivation have a positive and significant influence on employee performance. In addition, job satisfaction is proven to mediate the relationship between training and motivation with employee performance. Good training and high motivation increase job satisfaction, which in turn has an impact on improving employee performance. This research is expected to make a practical contribution to organizations in formulating strategies to improve employee performance through effective training and providing the right motivation. Theoretically, this research also adds insight into the relationship between training, motivation, job satisfaction, and employee performance. Keywords: Training, Motivation, Job Satisfaction, Employee Performance